ANALYSIS OF INTENSIFICATION OF HEAT EXCHANGE USING A SPIRAL SPRING - B. J. Khursanov (Modern American Journals, 2025)
The article presents problems of heat exchange processes and devices and ways to solve them. Methods of intensifying processes in spiral-ring heat exchangers are analyzed. Turbulizers transform the boundary layer of the heat carrier on the inner surface of the pipes into a vortex and absorb it, as a result of which the thermal resistance decreases and the heat transfer process accelerates.
Keywords: Heat exchange, heat transfer agent, spiral-spring, spiral twist angle, internal surface, heat transfer coefficient, intensification method.